Effect of combination of ethylenediaminetetraacetic acid + tetracycline with coronally positioned flap in the treatment of gingival recession: A clinical study - Lahari Buggapati; Vijay Kumar Chava (Wolters Kluwer Medknow Publications, 2016)
Context: Gingival recession is the apical migration of gingival margin results from destruction of the connective tissue leading to various esthetic problems. Many surgical procedures have been attempted to achieve root coverage that include free gingival grafts, pedicle flaps such as semilunar coronally repositioned flaps (SCRFs) and guided tissue regeneration. The exposed root surface has undergone substantial alterations and may no longer serve as an appropriate substrate for cell attachment and fiber development. When the denuded root surfaces are treated with biomodifiers following mechanical instrumentation, the resulting surface favors both the attachment of fibroblasts and new connective tissue attachment. It was then necessary to evaluate the surface characteristics of the acid demineralized root surface and its effect on periodontal wound healing. Aim: To evaluate the effect of the combination of ethylenediaminetetraacetic acid (EDTA) and tetracycline as root bio-modifiers along with SCRF for root coverage. Settings and Design: Twenty subjects were randomly assigned into two groups as cases (SCRF + EDTA + tetracycline [TTC]) and controls (SCRF). Materials and Methods: Twenty-four percentage EDTA and 100 mg/ml TTC hydrochloride were used along with semilunar coronally positioned flap. The clinical parameters such as recession height, the width of keratinized tissue, recession width, clinical attachment level, probing depth, plaque index, and gingival index were recorded at baseline, 1 and 3 months. Statistical Analyses Used: The clinical parameters were compared using post-hoc test and the comparison between cases and controls was done using Mann-Whitney U-test. Results: No statistical significant difference has been observed between the groups. Conclusion: It was concluded that no clinical benefit was observed after the application of a combination of 100 mg/ml TTC hydrochloride and 24% EDTA on the root surface.